Influence of seasonal variations on the survival of dairy calves of mixed breeding - Matta, Hildo (Pesquisa Agropecuaria Brasileira, 2014)
Data on 1,312 calves from a dairy herd of mixed breeding, born during a ten-year period (1959-67 and 1970) were used in this study. The calves were raised in typical ecological conditions of the Baixada Fluminense area, Itaguaí County, State of Rio de Janeiro, Brazil. To determine the association between season of birth as influenced by seasonal climatic variations and the survival rate of the calves, the year was divided into 4 periods, selected from among 3 possible month combinations through the application of the X2 Test. The periods selected were: 1) December-January-February; 2) March-April-May; 3) June-July-August, and 4) September-October-November. Periods 1 and 4 are most representative of the hot rainy season, while periods 2 and 3 represent the dry pleasant season. The calves that were born during Periods 2 and 3 presented the highest survival rates (P < 0.05). Period 2 was more favorable to survival of the calves than was Period 3 (P < 0.05), while there was no significant difference between Periods 1 and 4 of the hot rainy season. However, both of these periods were inferior to Period 2. Period 2 also was considered the most desirable from the standpoint of the economic interests of the dairy farmer and the commercialization of the milk.